Exploring Fast Food Consumption Pattern in Relation to Sociodemographic Factors Among School Going Adolescent (Journal of Dentistry and Allied Science, 2023)
Background: Diet plays a very important role in growth and development of adolescents. Consumption of fast food among adolescents is rising day by day in Bangladesh. Though its adverse health consequences are widely prevalent in all age groups but adolescents are more at risk. The objectives of the study was to determine fast food consumption pattern among school going adolescent in Dhaka, Bangladesh. Methods: This cross sectional study was conducted from January to December 2022. Sample size was 312 adolescent from two secondary schools in Dhaka. Convenience sampling technique was followed for data collection by face to face interview by using a pretested, semi-structured questionnaire. Data were edited through checking and rechecking for quality control. Data were analyzed by Statistical software. Results: Among 312 adolescent, the mean±SD age was 14.91±1.17 years. Majority of the adolescent were female (54.2.%) and Muslim (95.8%). The profession of fathers of 60.3% respondents were businessman and of 36.5 respondents were service holder. The majority (73.7%) of the respondents took breakfast before going to school, 53.8% took tiffin from school canteen and 53.5% ate snacks once in a day. The majority (59.7%) ate fast food weekly. Among the adolescent 47.2% ate burger, 28.7% ate pizza, 17.7% ate sandwich,30.4% ate chicken grill one time in a week. Among the adolescent 92.6% liked soft drinks when consumed fast food. Significant association were found between respondents’ family monthly income and frequency of eating fast food (p